Development of quality-oriented management ideology : a longitudinal case study on the permeation of quality ideology in two Finnish family-owned manufacturing companies - Savolainen, Taina (1997)
The aim of the present study has been to explore how and why a management ideology develops in an organization over time. In this study it is examined as the spreading and shaping of quality-oriented management ideology. The conceptual framework for studying the ideological change process was constructed by gathering ideas across disciplines, from the concepts of Political Science and the History of Ideas. The concept of ideology was applied as a heuristic idea. Quality was seen as a management ideology, the purpose of which is to exert influence on management thinking and to improve managerial practices. An ideology was viewed as a historically changeable, evolving movement, manifesting itself at the idea and real world levels. This starting point directed the specifying of the research problem to the permeation of quality ideology which formed the core focus of the empirical study. As an organization theoretical phenomenon, the permeation of quality ideology was examined as a form of organizational revitalization. Managerial paradigm change formed the sub-perspective on organizational revitalization, especially juxtaposed against mechanistic managerial thinking. Methodologically, this study can well be categorized as inductive type of research. The approach is both dynamic and historical at the same time. The empirical research task is conducted as a longitudinal, historical two-case study based on interviews and written material. At the real world level quality ideology was studied from two perspectives: a macro-perspective, as a national management ideological movement, and a micro-perspective, as an organizational permeation process in two companies. A macro-level investigation resulted in a developmental picture of the Finnish quality movement, up to now unexplored in the suggested form. This provided the necessary background for the organization-level investigation which formed the primary task of this study. The development of quality ideology at the micro-level was studied in two family-owned manufacturing firms from the early 1980s to the mid-90s. The process was described by two main dimensions: 1) the spreading, and 2) the shaping of quality ideology. The key result of this study was the three emerging company-specific modes of spreading quality ideology induced from the empirical data. They were labeled as archetypes and named as follows: 1) the coach-leadership, "pioneering" mode, 2) the oscillating, "professionally-driven" mode, and 3) the leader-expert mode, ("by the book"; leader-driven, expert-fed cooperation and confidence). The study also produced a refined conveyance model of quality ideology in which intellectual fields and the role of different actors were identified and analyzed. The dynamics of the permeation process of quality ideology was revealed in this study. It resulted in the dynamic process model of permeation, suggesting that the company-specific modes are shaped by distinct inner and outer contexts, actors, and the time factor. The primary impetus of adopting quality ideology is the external environment, more specifically, customer demands and the development of the economy. The former seems to be the more powerful force in the long run and the latter apparently sets the pace in the short run. Internal, organizational factors include type of organization, culture, structure and size of organization, the nature of business, individual managerial and nonmanagerial actors and the coalition of the actors in the process. Of internal explanations, the actor perspective proved to be relevant in explaining processual patterns, especially, as analyzed in the context of organizational type. The findings resulted in five concluding propositions with four managerial implications. In conclusion, this study indicates that the process of entry and permeation of a new managerial ideology in an organization occurs differently in different businesses, and even differs between business units within the same ownership structure but different of types of businesses in the concern studied. Ideas of quality basically enters the organization from outside. The company-specific modes show that different strategies are followed in pursuit of "becoming wiser in managing quality": 1) leader-driven, supported by cooperation with the supplying expert; 2) driven by the dominant "coaching" managerial actor through indigenous pioneering efforts and in cooperation with organization members; 3) through trial and error, by oscillations, forces and counterforces, by means of non-managerial internal professionals and with the cooperation of managerial actors. In the permeation process there are different types of actors, managerial and nonmanagerial, in organizational intellectual fields, in different combinations and with distinct degrees of influence. It appears that no single actor conveys wisdom but different actors and distinct coalitions of them do. Top and upper management's influence as a mediatory element determines the attitude toward new doctrines and develops into a binding element in the permeation process. Organizational culture, in tum, seems to form a binding force through which a managerial mediator functions. Managerial influence was combined with co-mediating, non-managerial influence in one of the cases studied. A nonmanagerial actor functions with the management and through a specific, cooperation/confidence mode of action. Organizational type, in these illustrations, reflects the entrepreneurial spirit as a force of development. It seems to explain a continuous pursuit of "qualitization" in these family-owned businesses. Furthermore, this study discloses that quality management ideology develops incrementally and by company-specific cycles. The cyclical development progresses at different speed and with varying intensity in different companies. This implies the notion of embeddedness (the degree of implantation) which is connected with the degree of managerial influence, and the organizational and environmental context. From the perspective of paradigm change, this study provides some insights into managerial change in organizations. The Tayloristic paradigm as a mechanistic organizational model is challenged by some findings of this study. It makes possible an interpretation different from what some prior findings have suggested. It is proposed in this study that the advantageous infusion of quality ideology begins to dislodge the established elements of the managerial paradigm. Two of the cases studied reflect the organismic, cultural mode of implementation. These particular cases show that the "qualitization process" incrementally reorients organizational processes and systems - departing from Taylorism - through which business performance is achieved while the ultimate ends of business remain. Finally, these findings support the notion that an embedded ideology provides a mental buffer in drastic environmental changes by facilitating the organization's adaptation to it. The notion of shallowness is also proposed which suggests that a non-rooted ideology proves to be even a threat under strong external pressure.